The macroeconomic effects of public debt : an empirical analysis of Mozambique - Afonso, António (2018)
Public debt has been rising markedly over the years, which suggests an increase in public expenditure financed by debt instead of taxation. There is no consensus on the economic implications of borrowing to finance public expenditure. We assess empirically the macroeconomic effects of public debt for the case of Mozambique over the period of 2000Q1- 2016Q4. We use a Vector Autoregression model to assess these effects through impulse response functions and variance decomposition. We conclude that debt service variables have much more negative effects on this economy than debt variables. Debt variables over the period of this study had no significant impact on the real output and the debt service component depressed the real output, increased the general price level and accounted for the depreciation on the domestic currency.